Total Quality Management, Reward System and Environmental Uncertainty on Managerial Performance - Poernomo, Hadi; Suryadnyana, Nyoman Adhi; Sjam, Juska Meidy Enyke; Supriadi, Taufiq (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The primary objective of this study is to assess the impact of Total Quality Management, the reward system, and environmental uncertainty on managerial performance. This research had a sample of 81 participants who were selected from 81 organizations that implement Total Quality Management (TQM) and have obtained the International Organization for Standardization (ISO) certification, namely the Indonesian National Standard (SNI). To ascertain the sample size, the selected sample criteria consist of one respondent who holds the Production Manager or Marketing Manager role within each organization. The utilized data source consists of primary data directly obtained by researchers from respondents through administering a questionnaire instrument. The proposed data analysis approach examines the research instrument, including validity and reliability tests. The use of multiple linear regression analysis, t-tests, and f-tests will come after performing traditional assumption tests. The introduction of Total Quality Management (TQM) and the development of a reward system have had a noteworthy and favorable impact on managers' performance within several Manufacturing Companies situated in the Nusantara Bonded Zone. This finding substantiates the significance of allocating resources to implement effective quality management strategies and providing suitable incentives to enhance managerial performance. On the other hand, it is noteworthy that environmental uncertainty exerts a substantial adverse impact on managerial performance, underscoring the imperative for organizations to possess the capability to predict and effectively navigate this uncertainty to sustain optimal performance levels.